PERAN PENYULUHAN PERTANIAN DALAM MEMBENTUK PERILAKU PETANI DI KABUPATEN ENDE - Reyna Virginia Nona; Estherlina Sagajoka (ANALISIS, 2021)
Agricultural extension agents play an important role in the implementation of agricultural extension activities. The success of agricultural extension activities will be seen in the behavior of farmers, where there is an increase in farmers' knowledge, attitudes and skills. This study aims to determine the role of the implementation of agricultural extension in shaping farmer behavior. The analytical tool used is descriptive statistics, which begin with weighting and then score using a Likert scale. In order to increase the measurement from the ordinal scale to the interval scale, the Method Successive Interval was used. 150 farmers were sampled in this study and spread across ten sub-districts out of eighteen sub-districts in Ende District. The results showed that the implementation of agricultural extension had a significant role in shaping farmer behavior consisting of knowledge, attitudes and skills. The components that need to be improved by farmers are cultivation knowledge, technical, managerial skills, and business partnerships, so that good extension knowledge is needed about the characteristics of the production area, the availability of facilities and infrastructure, building partnerships and mutual trust among farmers, extension workers, academics and the businessmen.